Healthcare staff's views on responding to suicide and self‐harm: Part I. Issue 4 (22nd February 2021) - Kilty, Caroline; Goodwin, John; Hartigan, Irene; Meehan, Elaine; Murphy, Margaret; Dillon, Christina; Heffernan, Sinead; Hegarty, Josephine; Greaney, Sonya; O'Brien, Maidy; Chambers, Derek; Twomey, Una; et al.
Abstract: Purpose: To explore healthcare staff's knowledge and awareness of, and responses to, suicide and self‐harm. Design and Methods: A qualitative design was adopted, and data were collected using a "World Café" approach ( n  = 143 participants), in addition to written submissions ( n  = 10). Data were analyzed using reflexive thematic analysis. Findings: There was variation relating to awareness of and responses to suicide and self‐harm. Participants highlighted the need for further staff education and training, and a review of standardized assessment tools and referral processes. Practice Implications: Tailored training and education resources are required for healthcare staff. Clear protocols for assessing, treating, and referring people deemed at risk of suicide and self‐harm are needed.